Diffuse Alveolar Hemorrhage in a Patient with Antisynthetase Syndrome - D. A. Vargas-Gutiérrez; F. Solís-Jiménez; K. I. Arias Callejas; L. Cano Cruz; R. Zapata Arenas; A. O. Acero López; P. Puente Rodríguez; S. Velázquez de la Paz (Case Reports in Rheumatology)
An alveolar hemorrhage case is reported as the initial manifestation of antisynthetase syndrome in a 40-year-old man, who is admitted to the Emergency Department for diagnostic approach of chronic cough and progressive dyspnea. The diagnosis of the alveolar hemorrhage was based on the presence of acute respiratory failure, decrease in hemoglobin levels, and observation of macrophages filled with hemosiderin. The antisynthetase syndrome was classified through a tomographic image compatible with a nonspecific interstitial pneumonia, along with antibodies associated to myositis (PL-12 and Ro-52). The study protocol was completed with the result of a myopathic pattern showed in electromyography. This patient presented a good response to steroids and disease-modifying antirheumatic drug (DMARD).